AKSEPTASI ELECTRONIC TICKETING: STUDI PADA PT. KERETA API INDONESIA (Persero) - , DEGA TRIANGGORO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The needs to develop the electronic ticketing (e-ticketing) using the world wide web (www) is important given the increasing use of the Internet. This study analyzes the acceptance of e-ticketing facility, with PT. Kereta Api Indonesia (Persero) railways customers as research objects in order to find empirical evidence about the influence of Trust (TRU), Intention to Transact (INT), Perceived Usefulness (PU), Perceived Ease of Use (PEU) , Perceived Enjoyment (PE), Information on E-Ticketing (INE), Security and Privacy (SP), and the Quality of Internet Connection (QIC) on Kereta Api Railways consumer acceptance using the Technology Acceptance Model (TAM). This study uses primary data by giving questionnaires to 270 passengers Kereta Api, which has been using the electronic ticket system. Data were analyzed by Structural Equation Model (SEM) using AMOS 19. This study shows that ease of use does not influence significantly to intention to Transact and e-ticketing facility acceptance due to the geographical condition of Yogyakarta is relatively small so that customers prefer to buy the ticket directly. Besides that the quality of internet connection also does not influence significantly to electronic system acceptance because customers not yet accustomed to using online media, so that good internet connection is still unable to attract customers for using e-ticketing services.